Analisis Strategi Pembelajaran Active Knowledge Sharing dan Ceramah Terhadap Hasil Belajar Pendidikan Agama Islam - Hanum, Latifah (Prodi PAI STAI Sumatera Medan, 2020)
The aims of this study are to compare learning outcomes of Islamic Religious Education using active knowledge sharing learning strategies and lecture strategies. This research was conducted at MTs Bina Taruna Marelan with 60 students as the sample in this study. The research method used in this study is a quantitative method with the type of experiment. The main instrument used in data collection is an objective test instrument consisting of 20 questions. The material provided is about Zakat Fitrah and Malls. The comparative analysis used is the t test statistic for two large samples which do not have a relationship with each other. The results showed that learning outcomes using active knowledge sharing learning strategies obtained an average value of 73.50 included in category B (good). While using lecture learning strategies obtained an average value of 62.83 included in category C (enough). So that the active knowledge sharing learning strategy is more effective by 16.88% of the lecture learning strategy in improving the learning outcomes of Islamic Religious Education grade VII students of MTs Bina Taruna Marelan.